2017
DOI: 10.1016/j.jid.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte-Derived Chemokines Orchestrate T-Cell Positioning in the Epidermis during Vitiligo and May Serve as Biomarkers of Disease

Abstract: Vitiligo is an autoimmune disease of the skin that results in the destruction of melanocytes and the clinical appearance of white spots. Disease pathogenesis depends on IFN-γ and IFN-γ-induced chemokines to promote T cell recruitment to the epidermis where melanocytes reside. The skin is a complex organ, with a variety of resident cell types. We sought to better define the microenvironment and distinct cellular contributions during autoimmunity in vitiligo, and found that the epidermis is a chemokine-high nich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
156
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 151 publications
(169 citation statements)
references
References 31 publications
11
156
0
2
Order By: Relevance
“…7,1316,23 Originally, we hypothesized that inhibition of IFN-γ signaling using JAK inhibitors would lead to repigmentation, and results of 2 patients 19,20 using 2 different oral JAK inhibitors, tofacitinib and ruxolitinib, supported this hypothesis. Recently, a case series evaluating topical ruxolitinib also demonstrated efficacy 21 .…”
Section: Discussionmentioning
confidence: 99%
“…7,1316,23 Originally, we hypothesized that inhibition of IFN-γ signaling using JAK inhibitors would lead to repigmentation, and results of 2 patients 19,20 using 2 different oral JAK inhibitors, tofacitinib and ruxolitinib, supported this hypothesis. Recently, a case series evaluating topical ruxolitinib also demonstrated efficacy 21 .…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 was elevated in the non-lesional skin of some subjects, which could be partially from blister trauma and might explain why it is a less specific marker using this method. Alternatively, CXCL9 protein may be more bioavailable for detection by ELISA than CXCL10 in blister fluid based on their different spatial and temporal expression in the skin 23 , binding affinities to structural elements 24,25 , and/or oligomerization within tissues 26 . We previously reported that both CXCL9 and CXCL10 had functional roles in our mouse model of vitiligo, however only CXCL10-deficient mice were protected from clinical disease 4 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that both CXCL9 and CXCL10 had functional roles in our mouse model of vitiligo, however only CXCL10-deficient mice were protected from clinical disease 4 . Although both chemokines are expressed in active disease, they are produced by different cell types and with different kinetics during vitiligo progression 23 . CXCL9 is expressed earliest in murine vitiligo lesions and may be a more specific marker of disease activity 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in skin lesions, CTL remarkably infiltrate into the epidermis and accumulate around the dying melanocytes . Generally, CTL migrate into the skin following various chemokine signals . Chemokines are important inflammatory factors that participate in many autoimmune responses.…”
Section: Introductionmentioning
confidence: 99%